This action might not be possible to undo. Are you sure you want to continue?

CANCEL

OK

Welcome to Scribd. Sign in or start your free trial to enjoy unlimited e-books, audiobooks & documents.Find out more

Download

Standard view

Full view

of .

Look up keyword

Like this

Share on social networks

3Activity

×

0 of .

Results for: No results containing your search query

P. 1

Pset Complex Variables 2.9Ratings: (0)|Views: 2,061|Likes: 1

Published by Joseph M. Stahl

Complex Variables PSet

Complex Variables PSet

See more

See less

https://www.scribd.com/doc/80583557/Pset-Complex-Variables-2-9

03/03/2013

text

original

P-SET FOR MA412 DUE 2/9/2012

JOE STAHL

1.

18.3

Let

n

be a positive integer and let

P

(

z

) and

Q

(

z

) be polynomials, where

Q

(

z

0

)

= 0. Use Theorem2 in Sec. 16, as well as limits appearing in that section, to ﬁnd(a) lim

z

→

z

0

1

z

n

(

z

0

= 0)If

z

0

= 0, then

z

n

is continuous and nonzero at

z

0

, and is nonzero in a neighborhood of

z

0

(bytheorem 18.2). Then by theorem 16.2, taking

f

(

z

) = 1 and

F

(

z

) =

z

n

, we have

f

(

z

0

) = 1 andlim

z

→

z

0

F

(

z

0

) =

z

n

0

= 0, solim

z

→

z

0

1

z

n

=1

z

n

0

(b) lim

z

→

i

iz

3

−

1

z

+

i

Referring to theorem 16.2 with

f

(

z

) =

iz

3

−

1 and

F

(

z

) =

z

+

i

, we see that lim

z

→

i

f

(

z

) =

i

·

i

3

−

1 = 0and lim

z

→

i

F

(

z

) =

i

+

i

= 2

i

= 0, solim

z

→

i

iz

3

−

1

z

+

i

=02

i

= 0(c) lim

z

→

z

0

P

(

z

)

Q

(

z

)Appealing again to theorem 16.2 and taking

f

(

z

) =

P

(

z

) and

F

(

z

) =

Q

(

z

), we see lim

z

→

z

0

P

(

z

) =

P

(

z

0

) and lim

z

→

z

0

Q

(

z

) =

Q

(

z

0

)

= 0, solim

z

→

z

0

P

(

z

)

Q

(

z

)=

P

(

z

0

)

Q

(

z

0

)2.

18.5

Show that the limit of the function

f

(

z

) =

zz

2

as

z

tends to 0 does not exist. Do this by letting nonzero points

z

= (

x,

0) and

z

= (

x,x

) approachthe origin. Let

P

1

be the path that tends to 0 along the

x

axis, that is, the path deﬁned by

z

= (

x,

0),

x

∈

R

. Then the limit as

z

tends to 0 along

P

1

islim

x

→

0

x

+

i

0

x

−

i

0

2

= lim

x

→

0

xx

2

= lim

x

→

0

1 = 1

1

2 JOE STAHL

Let

P

2

be the path that tends to 0 along the line

x

=

y

(deﬁned by

z

= (

x,x

),

x

∈

R

. Then thelimit as

z

tends to 0 along

P

2

islim

x

→

0

x

+

ixx

−

ix

2

= lim

x

→

0

x

(1 +

i

)

x

(1

−

i

)

2

= lim

x

→

0

1 +

i

1

−

i

=1 +

i

1

−

i

= 1Since the two limits are not equal, the limit in question does not exist.3.

20.1

Use results in Sec. 20 to ﬁnd

f

(

z

) when(a)

f

(

z

) = 3

z

2

−

2

z

+ 4

f

(

z

) = 2

·

3

z

1

−

1

·

2

z

0

+ 0= 6

z

−

2(b)

f

(

z

) =

1

−

4

z

2

3

f

(

z

) = 3

·

1

−

4

z

2

2

·

−

2

·

4

z

1

=

−

24

z

1

−

4

z

2

2

(c)

f

(

z

) =

z

−

12

z

+ 1(

z

=

−

12)

f

(

z

) =1

·

(2

z

+ 1)

−

(

z

−

1)

·

2(2

z

+ 1)

2

(

z

=

−

12)=3(2

z

+ 1)

2

(

z

=

−

12)(d)

f

(

z

) =

1 +

z

2

4

z

2

(

z

= 0)

f

(

z

) =4

·

1 +

z

2

3

·

(2

·

z

)

·

z

2

−

2

·

z

·

1 +

z

2

4

(

z

2

)

2

(

z

= 0)=2

1 +

z

2

3

3

z

2

−

1

z

3

(

z

= 0)

P-SET FOR MA412 DUE 2/9/2012 3

4.

20.3

Apply deﬁnition (3), sec. 19, of derivative to give a direct proof that

dwdz

=

−

1

z

2

when

w

=1

z

(

z

= 0)∆

w

=1

z

+ ∆

z

−

1

zdwdz

= lim

∆

z

→

0

∆

w

∆

z

= lim

∆

z

→

01

z

+∆

z

−

1

z

∆

z

= lim

∆

z

→

0

z

−

∆

z

−

zz

(

z

+∆

z

)

∆

z

= lim

∆

z

→

0

−

∆

z

∆

z

·

z

(

z

+ ∆

z

)= lim

∆

z

→

0

−

1

z

(

z

+ ∆

z

)=

−

1

z

(

z

+ 0)=

−

1

z

2

(

z

= 0)5.

20.4

Suppose that

f

(

z

0

) =

g

(

z

0

) = 0 and that

f

(

z

0

) and

g

(

z

0

) exist, where

g

(

z

0

)

= 0. Use deﬁnition(1), Sec. 19, of derivative to show thatlim

z

→

z

0

f

(

z

)

g

(

z

)=

f

(

z

0

)

g

(

z

0

)If

f

(

z

0

) =

g

(

z

0

) = 0, then

f

(

z

)

g

(

z

)

=

f

(

z

)

−

f

(

z

0

)

g

(

z

)

−

g

(

z

0

)

. Also note that if

z

=

z

0

, then

f

(

z

)

g

(

z

)=

f

(

z

)

−

f

(

z

0

)

g

(

z

)

−

g

(

z

0

)=

f

(

z

)

−

f

(

z

0

)

g

(

z

)

−

g

(

z

0

)

·

z

−

z

0

z

−

z

0

=

f

(

z

)

−

f

(

z

0

)

z

−

z

0

g

(

z

)

−

g

(

z

0

)

z

−

z

0

Thus,lim

z

→

z

0

f

(

z

)

g

(

z

)= lim

z

→

z

0

f

(

z

)

−

f

(

z

0

)

z

−

z

0

g

(

z

)

−

g

(

z

0

)

z

−

z

0

=lim

z

→

z

0

f

(

z

)

−

f

(

z

0

)

z

−

z

0

lim

z

→

z

0

g

(

z

)

−

g

(

z

0

)

z

−

z

0

=

f

(

z

0

)

g

(

z

0

)Because by assumption

f

(

z

0

) and

g

(

z

0

) exist, this holds true and we are done.

- Read and print without ads
- Download to keep your version
- Edit, email or read offline

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

CANCEL

OK

You've been reading!

NO, THANKS

OK

scribd